KH. Ahmad Dahlan and Islamic Education: An Effort to Spread Islam Raḥmat li’l-‘Ālamīn - Ahmad Nurul Huda & Abdullah Affandi (Pascasarjana Universitas Wahid hasyim Semarang, 2015)
This study tries to investigate Ahmad Dahlan’s educative role and struggle in improving the Muslim quality. As we have known, there are a number of schools and higher institutions under the patronage of Muhammadiyah organization founded by Ahmad Dahlan. This reality could not absolutely be separated from his vision and mission. This research uses a descriptive analytic. It has reached on the hypothesis that Ahmad Dahlan religious propagation (da’wah) is more practical and applicative than formalist-textualist for example when he interprets Surah al-Ma’un, the language approach he used is not rigid. On the contrary, he placed himself as motivator and activator for his people to move together to help poor people and orphan and to demulcent another’s burdens as has been taught by such verses.Keywords: Islamic education; Islam; Ahmad Dahlan; peace in world